2017
DOI: 10.1177/1055665617718840
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Representations and Parenting Style in Children Born With and Without an Orofacial Cleft

Abstract: Objective: To investigate the evolution of maternal representations (ie, the way parents perceive their child in term of temperament, character, behaviors, etc) of children with a cleft at 3 major milestones: before/after reconstructive surgeries and at school age. Parenting style was also analyzed and compared with parents of children born without a cleft. Design and participants: The sample was composed of 30 mothers of children with an orofacial cleft and 14 mothers of children without a cleft. Maternal rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Although recent qualitative work has offered in-depth reports of families’ experiences of the treatment journey (eg, Vanz and Ribeiro, 2011; Nelson et al, 2012; Nelson and Kirk, 2013; Stock and Rumsey, 2015), the quantitative literature is characterized by conflicting findings. Although some studies have observed high levels of parental stress and depression (eg, Habersaat et al, 2018), others have reported few differences in family functioning between parents of children with CL/P and the general population (eg, Crerand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent qualitative work has offered in-depth reports of families’ experiences of the treatment journey (eg, Vanz and Ribeiro, 2011; Nelson et al, 2012; Nelson and Kirk, 2013; Stock and Rumsey, 2015), the quantitative literature is characterized by conflicting findings. Although some studies have observed high levels of parental stress and depression (eg, Habersaat et al, 2018), others have reported few differences in family functioning between parents of children with CL/P and the general population (eg, Crerand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Giving birth to an infant with a cleft also is a source of stress for parents, and this is often followed by parental distress (Bradbury & Hewison, ; Despars et al., ; Habersaat et al., ; Johansson & Ringberg, 2004), at least temporarily affecting the parental attachment representations (Habersaat et al., ). Most parents experience feelings of grief and loss concerning the unanticipated appearance of the child as well as fear about the child's future (Endriga & Kapp‐Simon, ; Hasanzadeh, Khoda, Jahanbin, & Vatankhah, ; Locker et al., ; Weigl, Rudolph, Eysholdt, & Rosanowski, ).…”
mentioning
confidence: 99%